Analisis Framing Pemberitaan di Rubrik “Politika” SKH Media Kalimantan tentang Calon Legislatif pada Pemilu 2014 - Favi Aditya Ikhsan (Syams, 2021)
This article explores the news on legislative candidates in the 2014 electionin local media, SKH Media Kalimantan, specifically in the “Politics”rubric. The author uses a descriptive type of research using qualitativemethods. The author dissects the news text in each title by using framinganalysis (with the model from Pan & Kosicki). The news on legislativecandidates (calon anggota legislatif, caleg) which was publishedspecifically on the “Politics” rubric page at SKH Media Kalimantan is notthe actual reality, but a representation of reality that has undergone aprocess of selection, sorting, protrusion, refraction, construction, &reconstruction. The author concludes that the framing and attitude of SKHMedia Kalimantan in reporting on legislative candidates found in this studyis a reflection of the political side of the media owners behind the editorialside of SKH Media Kalimantan. Gatekeepers within SKH Media Kalimantanseem to be biasing news about candidates who share the same politicalideology as the media owner SKH Media Kalimantan.